Association between Third Molar Agenesis and Other Dental Anomalies - parastoo namdar; atena shiva; mehran armin; tahura etezadi; reza ali mohammadpour; ali ajilian (Mashhad University of Medical Sciences, 2021)
Introduction: Third molar teeth are the most common teeth with agenesis. The absence of this tooth also increases the probability of anomalies in other teeth by several times. Since panoramic radiography is used to diagnose and plan treatment in orthodontic patients, along with routine clinical examination, this study aimed to determine the prevalence of third molar agenesis and incidence of other associated anomalies in comparison to that reported for the non-agenesis group using panoramic radiographs. Materials and Methods: In this descriptive-analytical study, the pretreatment records of 562 patients were randomly collected. Out of these subjects, 538 patients were selected based on inclusion and exclusion criteria. The panoramic radiographic images of patients who did not have at least one third molar were assessed with regard to the presence of other dental anomalies, such as dental agenesis, hypodontia, hyperdontia, impacted canine, peg-shaped lateral incisors, ectopic eruption, microdontia, dilaceration, transposition, and transmigration. The prevalence of these anomalies was compared to that of a randomized control group selected from patients with the presence of each four third molars. Results: Out of 538 studied panoramic radiographs, overall, 13.7%, 13.5%, 13.4%, 5.9%, 2.7%, and 1.4% of them had at least one third molar agenesis, canine impaction, peg-shaped lateral incisors, missing teeth, transposition, and hyperdontia, respectively. The frequency rates of impaction and missing teeth were higher in the agenesis group (30% and 40.5%) than those reported for the control group (16% and 2.7%) (p < /em>>0.001), respectively. The presence or absence of other dental anomalies was not statistically significant between the two groups and two genders. In addition, the present study demonstrated that the probability of the presence of at least one type of other dental anomalies was higher in individuals with third molar agenesis in comparison to that reported for the control group (p < /em>>0.001). Conclusion: Among different types of dental anomalies in the studied population, the probability of impaction and missing teeth was higher in the third molar agenesis group than that of the control group. Furthermore, the prevalence of third molar agenesis was not different between the two genders.